Fikih Siyasah: Bagaimana Sesungguhnya Konstruksi Pemahaman Perang dan Damai dalam Perspektif Islam - Ali Syahputra (LAKPESDAM MWCNU Palengaan, 2024)
This research aims to redefine the role of religion in facing the challenges of global conflict in this contemporary era. This research uses a qualitative method by involving academics and experts in fiqh politik for a deeper understanding. The data collected will be analyzed using the theory of